Buckling analysis of symmetrically-laminated plates using refined theory including curvature effects / Mokhtar Bouazza, Abdelaziz Lairedj and Noureddine Benseddiqd - Mokhtar Bouazza; Abdelaziz Lairedj; Noureddine Benseddiqd (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
A refined theory is successfully extended in this study for critical buckling loads of rectangular, symmetrically-laminated plates, including curvature effects. The theory accounts for a quadratic variation of the transverse shear strains across the thickness, and satisfies the zero traction boundary conditions on the top and bottom surfaces of the plate and avoids the need of shear correction factors. The numerical results are presented for critical buckling loads for orthotropic laminates subjected to biaxial inplane loading. Using the Navier solution method, the differential equations have been solved analytically and the critical buckling loads presented in closed-form solutions. The significant effects of curvature terms on buckling loads are studied, with various loading conditions and thickness-side ratio. Some exact buckling solutions for simplified cases with and without the inclusion of curvature terms are obtained and compared with results available elsewhere in literature.